Novel insight on marker genes and pathogenic peripheral neutrophil subtypes in acute pancreatitis - Zhang, Deyu; Wang, Meiqi; Zhang, Yang; Xia, Chuanchao; Peng, Lisi; Li, Keliang; Yin, Hua; Li, Shiyu; Yang, Xiaoli; Su, Xiaoju; Huang, Haojie (Frontiers in Immunology, 2022)
Acute pancreatitis is a common critical and acute gastrointestinal disease worldwide, with an increasing percentage of morbidity. However, the gene expression pattern in peripheral blood has not been fully analyzed. In addition, the mechanism of coronavirus disease 2019 (COVID-19)-induced acute pancreatitis has not been investigated. Here, after bioinformatic analysis with machine learning methods of the expression data of peripheral blood cells and validation in local patients, two functional gene modules in peripheral blood cells of acute pancreatitis were identified, and S100A6, S100A9, and S100A12 were validated as predictors of severe pancreatitis. Additionally, through a combination analysis of bulk-sequencing and single-cell sequencing data of COVID-19 patients, a pivotal subtype of neutrophils with strong activation of the interferon-related pathway was identified as a pivotal peripheral blood cell subtype for COVID-19-induced acute pancreatitis. These results could facilitate the prognostic prediction of acute pancreatitis and research on COVID-19-induced acute pancreatitis.